2022
DOI: 10.1007/s12072-022-10375-y
|View full text |Cite
|
Sign up to set email alerts
|

A somatic mutation-derived LncRNA signatures of genomic instability predicts the prognosis and tumor microenvironment immune characters in hepatocellular carcinoma

Abstract: Background:Hepatocellular carcinoma (HCC) is an aggressive carcinoma with genome instability. Long non-coding RNAs (LncRNAs) have been functionally associated with genomic instability in cancers. However, the identi cation and prognostic value of lncRNAs related to genome instability have not been explored in hepatocellular carcinoma. In this study, we aim to identify a genomic instability-related lncRNA signature for predicting prognosis and the e cacy of immunotherapy in HCC patients. Methods:According to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In a previous study, a risk score for disul dptosisrelated genes was established to predict prognosis and guide clinical treatment [19]. Although there are many studies on the use of lncRNAs as molecular biomarkers to predict the prognosis of HCC patients, no study has systematically used DRLs as molecular biomarkers to predict the prognosis of HCC patients [20][21][22][23]. To our knowledge, this is the rst study of the prognostic signature of DRLs to predict prognosis in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, a risk score for disul dptosisrelated genes was established to predict prognosis and guide clinical treatment [19]. Although there are many studies on the use of lncRNAs as molecular biomarkers to predict the prognosis of HCC patients, no study has systematically used DRLs as molecular biomarkers to predict the prognosis of HCC patients [20][21][22][23]. To our knowledge, this is the rst study of the prognostic signature of DRLs to predict prognosis in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…From an omics and bioinformatics point of view, we can broadly classify the approaches that have been developed to prioritize lncRNAs with a possible association with cancer into at least two categories: (1) an early integrative analysis of somatic variants with cancer driver potential that have an impact on the functional activity of lncRNAs associated with prognosis in cancer patients [37,38,[69][70][71], and (2) post-analysis integration strategies centered on the relationship between genome instability and lncRNAs with aberrant expressions associated with tumor prognosis [39][40][41][42][43][44][45] (Figure 2). A representative study was conducted to evaluate the potential impact of somatic mutations in human lncRNAs (denominated MutLncs) and their functional significance in cancer, interrogate the mutation profiles in genomic regions harboring lncRNA and their vicinity across 17 cancer types, and use an integrative pipeline to describe the significance of the MutLncs contribution to cancer [69].…”
Section: Approaches For Prioritizing Cancer Driver Lncrnas Using Soma...mentioning
confidence: 99%
“…Somatic mutations are also predictive factors for immunotherapy, and in addition to TMB, somatic mutations are considered predictive biomarkers for high-grade solid tumors. 8 It has been reported that The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) have provided a detailed description of the genetic landscape associated with PAAD. Our study uses TCGA and ICGC data to describe the somatic mutation characteristics of PAAD patients.…”
Section: Introductionmentioning
confidence: 99%